Avaliação da influência da martensita induzida por deformação na resistência à corrosão localizada no aço inoxidável austenítico AISI 304 - Zaikievicz, Julio Cezar Vieira (2019)
Stainless steels are alloys primarily composed of iron, chromium and nickel. Widely used due to its high mechanical strength and ductility combined with great corrosion resistance. When plastically deformed, they may exhibit the formation of deformation-induced martensite in their structure in their structure. This paper aims the objective of study the modification of the localized corrosion resistance of the stainless alloys caused by the formation of martensitic phase through plastic deformation. Austenitic AISI 304 stainless steel samples were analyzed without deformation, with reduction of 20, 35 and 50%, obtained by compression test. The microstructure was evaluated by metallography, and the formation of martensite α' was confirmed by XRD analysis. Corrosion resistance was analyzed by potentiodynamic polarization curves. The induction of martensite by deformation didn’t change the breaking potential of the passive film of the samples, however it reduced the current required to break the passive film in smaller deformation.